Bio-combustion of petroleum coke: The process integration with photobioreactors. (23rd February 2018) - Severo, Ihana A.; Deprá, Mariany C.; Barin, Juliano S.; Wagner, Roger; de Menezes, Cristiano R.; Zepka, Leila Q.; Jacob-Lopes, Eduardo
Highlights: Photobioreactor exhaust gases were used as oxidizers, fuels and nitrogen diluent. Photobioreactor exhaust gases enhance the thermal performance of combustion system. The process has potential to supply energy and fuel economy in industrial facilities. Abstract: The objective of this study is to develop a bio-combustion system integrated into a photobioreactor. Different oxidizers (a simulated industrial gas stream containing 5.5% O2, 18% CO2 and 76.5% N2, the atmospheric air and the photobioreactor exhaust gases in different residence times) were injected into the combustion chamber, and combustion temperature, combustion stability, heating rate, and fuel conversion were analyzed. The results have shown that the use of photobioreactor exhaust gases as oxidizer, biofuel, and nitrogen diluent in the combustion furnace, have increased the thermal efficiency of the system, with heating rates 30.5% and 45.8% higher than the atmospheric air and the simulated industrial gas stream, respectively. Thus, the integration of these processes could be considered a viable strategy to improve the combustion systems thermal performance, efficiently contributing to the sustainability and economy of industrial operations.